2019
DOI: 10.1051/matecconf/201925801002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of density and height of vegetation in open channel on the Manning’s coefficient

Abstract: One of an important parameter to study water flow in channel is Manning’s coefficient (n). This coefficient is produced not only from material forming the channel, but also due to presence of vegetation in channel. The aim of research is to study the effect of vegetation density and height on Coefficient of Manning in open channel. The study was conducted in open channel with 15.5 m long, 0.5 m wide and 1.0 m high. At the center of 3 m long of channel is planted with Sweet flag (Acorus calamus). The impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The Reynolds stress increased at the downstream end of the interface section because of higher velocity fluctuations between the vegetated and un-vegetated zones. Rizalihadi [29] studied the effect of vegetation height and density on Manning's Coefficient in an open channel. The results indicated that denser and higher vegetation signified a greater decrease in the mean velocity in the range of 28.68-43.82%.…”
Section: Introductionmentioning
confidence: 99%
“…The Reynolds stress increased at the downstream end of the interface section because of higher velocity fluctuations between the vegetated and un-vegetated zones. Rizalihadi [29] studied the effect of vegetation height and density on Manning's Coefficient in an open channel. The results indicated that denser and higher vegetation signified a greater decrease in the mean velocity in the range of 28.68-43.82%.…”
Section: Introductionmentioning
confidence: 99%